The meaning of justified subjectivism and its role in the reconciliation of recent disagreements over forensic probabilism. Issue 6 (November 2017) - Biedermann, A.; Bozza, S.; Taroni, F.; Aitken, C.
Abstract: In this paper we reply to recent comments in this Special Issue according to which subjective probability is not considered to be a concept fit for use in forensic evaluation and expert reporting. We identify the source of these criticisms to lie in a misunderstanding of subjective probability as unconstrained subjective probability; a lack of constraint that neither corresponds to the way in which we referred to subjective probability in our previous contributions, nor to the way in which probability assignment is understood by current evaluative guidelines (e.g., of ENFSI). Specifically, we explain that we understand subjective probability as a justified assertion, i.e. a conditional assessment based on task-relevant data and information, that may be thought of as a constrained subjective probability. This leads us to emphasise again the general conclusion that there is no gap between justified (or, reasonable) subjective probability and other concepts of probability in terms of its ability to provide assessments that are soundly based on whatever relevant information available. We also note that the challenges an expert faces in reporting probabilities apply equally to all interpretations of probability, not only to subjective probability.